2020
DOI: 10.1021/acsaem.0c01428
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Water Splitting Using a Concentrated Solar Flux-Assisted LaFeO3 Photocathode

Abstract: Photoelectrochemical (PEC) water splitting by direct solar irradiation has been considered as a route to produce solar fuel, but the technique is impeded by limitation of the photocathode materials. Although the LaFeO 3 photocathode has been identified as a potential candidate for hydrogen generation with excellent stability, lower current densities limit its PEC performance. Using solar concentration could prove to be an effective method to leverage its performance. In this study, we have developed a strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have indicated that photovoltage improves with increasing solar concentration for various PEC systems. 6,7,9 The onset potential, as defined in Section S2.6 in the ESI,† is plotted in Fig. 5 and displays a similar trend.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies have indicated that photovoltage improves with increasing solar concentration for various PEC systems. 6,7,9 The onset potential, as defined in Section S2.6 in the ESI,† is plotted in Fig. 5 and displays a similar trend.…”
Section: Resultsmentioning
confidence: 71%
“…More recently, there has been a renewed interest in irradiance-dependence studies, but still limited to relatively low solar concentrations (<30 suns). Segev et al 6 and Gupta et al 7 performed comprehensive analysis of the performance of various doped Fe 2 O 3 films up to 25 suns and LaFeO 3 up to 18 suns, respectively. Both studies reported three-electrode experiments, which isolates the individual behaviour of the photoelectrode, and found that the photocurrent at maximum power point (where the photocurrent and photovoltage was defined as the difference between light and dark for current and applied potential, respectively) 8 was found to increase linearly with flux concentration, whereas the photovoltage at maximum power point was found to increase logarithmically.…”
Section: Introductionmentioning
confidence: 99%
“…3−8 According to various scientific repositories, in the year 2023, it has been reported that more than 540 research articles were published highlighting the use of LaFeO 3 nanoparticles (LFO NPs) in solid oxide fuel cells, CO 2 sensors, water splitting, and solar cells. 5,6,9,10 Thereby, LFO NPs as catalysts is on the verge of broad commercialization. In this regard, identifying an efficient and environmentally friendly approach for LFO synthesis is pivotal in avoiding the long-term impact on the environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Crystalline materials have been widely used in various fields such as photocatalysts, electrodes, biomaterials, heat conductors, and catalysts. , Functionalities of crystalline materials such as (opto)­electronic, intercalation, and catalytic properties strongly depend on the crystal structures as well as the particle size, exposed facets, and particle morphology; , which must be controlled to improve the functionalities. We focus here on the flux growth method of preparing crystalline materials, especially layered titanates.…”
Section: Introductionmentioning
confidence: 99%